MA'BADONG IN THE ARENA OF BOURDIEU'S CULTURAL PRODUCTION - Sambira, Zefanya; Palimbong, Andriano Mario; Rante Allo, Hasrat Dewi; Patalo, Jhesica (Institut Agama Kristen Negeri Toraja, 2025)
Ma'badong is a communal lament sung in a circular formation at the Toraja tribe's death ceremony (Rambu Solo'), serving as an expression of grief. Ma'badong is conducted following the slaughter of a tedong (water buffalo) in a quantity corresponding with the social rank of the deceased. Ma'badong is considered not only a symbolic gesture but also an endeavor to preserve and promote Toraja culture. This study aims to examine the contextualization of Ma'badong from the perspective of cultural production and its implications on the development of church music in Toraja. This research is characterized as descriptive and qualitative. This study examines the art of Ma'badong as portrayed in the Rambu Solo’ ceremony in Toraja, particularly in the Gandangbatu Sillanan District of Tana Toraja Regency. The analysis of the issues in this study is grounded in Pierre Bourdieu's theory, which is the Field of Cultural Production theory. The results of this study indicate that Pa'badong representatives, serving as both agents and traditional musicians in church music services, generate cultural practices appreciated by the Toraja community and church congregation members. The habitus of the Toraja community (Ma'badong) is shaped and regulated by agents based on the capital they hold, which enables them to exert dominance in the field of Toraja art, encompassing church music as well. The field controlled by agents is classified as an elite or limited cultural subfield. Ma'badong's implications for the development of church music in Toraja are the production of several ethnic-nuance congregational songs that incorporate its musical patterns and features. The incorporation of Ma'badong musical components has emerged as a significant characteristic of the Toraja Church, transforming congregational singing into a medium for expressing the local community's identity._______________________________________________________________________The page numbers for this article have changed from 140–162 to 92–114 due to pagination adjustments in the June 2025 issue. Consequently, the pages in the PDF file have been updated. Please note that metadata in indexing services may still reflect the previous page range; however, we have updated the official pages as required.